"She's My Partner in Crime": Informal Collaboration and Beginning Special Educator Induction. Issue 2 (3rd April 2021) - Chapman, Lindsey A.; Morris, Chelsea T.; Cavendish, Wendy
ABSTRACT: The shortage of special education teachers is a growing threat to the quality of education received by students with disabilities in the United States. The shortage is exacerbated by high rates of teacher turnover especially among beginning special educators (BSEs) assigned to teach in self-contained classrooms. To promote retention, greater focus is being given to the formal and informal induction experiences of BSEs. This study explored the informal mentoring relationship between one BSE and her mid-career colleague. The study's findings illustrate how these teachers initiated an informal collaboration that provided the reciprocal professional and personal support needed that was not provided by traditional professional development opportunities.